Health Effects of Waterpipe Tobacco Use: Getting the Public Health Message Just Right - Mohammed Ali; Mohammed Jawad (SAGE Publishing, 2017)
Many public health messages benchmark the harms of waterpipe tobacco against those of cigarettes, usually using numerical magnitudes of risk. This approach, although well intentioned, could be perceived as alarmist, damaging scientific credibility, and giving an unintended impression that one tobacco product is less harmful than the other. This commentary makes clear the harm waterpipe tobacco smoking poses to public health by describing its mechanism of use, consumption uptake, toxicologic profile, and documented health outcomes, as well as challenge existing thinking that toxicologic assessments are the most appropriate way to frame waterpipe tobacco health promotion messages. How can we describe the health effects of waterpipe tobacco without undermining its toxicity nor falling into the temptation of alarmist messaging? Several recommendations are provided.